2019
DOI: 10.1002/jms.4340
|View full text |Cite
|
Sign up to set email alerts
|

The pre‐separation of oxygen containing compounds in oxidised heavy paraffinic fractions and their identification by GC‐MS with supersonic molecular beams.

Abstract: The heavy petroleum fractions produced during refining processes need to be upgraded to useable products to increase their value. Hydrogenated heavy paraffinic fractions can be oxidised to produce high value products that contain a variety of oxygenates. These heavy oxygenated paraffinic fractions need to be characterised to enable the control of oxidation processes and to understand product properties. The accurate identification of the oxygenates present in these fractions by electron ionisation (EI) mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Several studies have reported that HT-GC uses a final temperature higher than 340°C. The HT-GC instrument, GC column, and stationary phase approach are operated at high temperature (Potgieter et al, 2019).…”
Section: Hs-gc-imsmentioning
confidence: 99%
“…Several studies have reported that HT-GC uses a final temperature higher than 340°C. The HT-GC instrument, GC column, and stationary phase approach are operated at high temperature (Potgieter et al, 2019).…”
Section: Hs-gc-imsmentioning
confidence: 99%
“…Currently, gas chromatography (GC) is the technique of choice when characterizing the molecular structure of hydrocarbon compounds in petroleum [25,26]. GC is the most efficient method for the analysis of volatile mixtures; the separation of compounds is achieved by the difference in molecular interaction between compounds in the carrier gas and the stationary phase of the column.…”
Section: Introductionmentioning
confidence: 99%
“…GC-MS with Cold EI improves all the central performance aspects of GC-MS and uniquely provides enhanced molecular ions, improved sample identification, significantly extended range of compounds amenable for analysis, uniform response to all analytes (internal quantitation), faster analysis, greater selectivity, and lower limits of detection [25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular ion is the most (and many times the only) characteristic ion as the fragmentation pattern can be similar for many compounds, and therefore it is often vital for sample compound identification. GC-MS with Cold EI improves all the central performance aspects of GC-MS and uniquely provides enhanced molecular ions, improved sample identification, significantly extended range of compounds amenable for analysis, uniform response to all analytes (internal quantitation), faster analysis, greater selectivity, and lower limits of detection [25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%